THE EFFECT OF GROUP GUIDANCE WITH ROLE PLAYING TECHNIQUES ON INCREASING STUDENT LEARNING MOTIVATION - Dimas; Muhammad Ferdiansyah; Yulianti (Program Studi Bimbingan dan Konseling FKIP UNJA, 2026)
This study aims to determine the effect of group guidance services with role playing techniques on increasing student learning motivation at SMA Negeri 4 Jambi City. Low student learning motivation is still found, characterized by a lack of active participation, learning discipline, and achievement motivation. This study uses a quantitative approach with a one group pretest-posttest experimental design. The research subjects were 10 students of class XI F9 who were selected by purposive sampling. Data were collected using a 25-item learning motivation questionnaire, using a Likert scale and analyzed using SPSS 27. The results of the instrument test in the initial pre-test obtained a score of 71.6, included in the moderate category with a score range of 50-66, in the post-test increased to 100.9, included in the very high category with a score range of 84-100.